Essays in social and economic development - Streeten, Paul. (New Delhi, 2010)
This volume contains 17 scholarly papers authored by Paul Streeten, the well-known American development economist and social thinker. Streeten's writings have assumed added significance in the context of both the globalization and privatization waves sweeping across the countries of the world, particularly the developing countries. In the immediate context, his ideas are relevant for understanding and dealing with the current global financial crisis, which has been billed by experts as the worst since the Great Depression of early the 1930s. The book covers a wide range of issues and concerns which have contemporary relevance for the social and economic development of countries worldwide. It discusses, reviews, and evaluates topical subjects, including poverty and hunger, global governance, cyber-terror, effects of globalization, international cooperation, global justice, empowerment of the disadvantaged, political economy reforms, the role of non-government organizations, and concerns raised by technological advancements including nanotechnology. The papers provide glimpses of Streeten's innovative ideas, such as a global central bank, a global income tax, a global body to provide information on investments, an international investment trust, and a global migration agency. Streeten also suggests a transnational secretariat and a council of wise men and women to monitor the performance of proposed bodies. He also delves on gender issues which he considers particularly important for reproductive freedom. The papers are valuable for researchers, teachers, students, and even laypersons who wish to understand current trends and issues in social and economic development of countries worldwide, particularly the developing economies of Asia.
Keywords: Economic development